Integrating Technology into The Social Work Education: Preparing Students for Digital Development - Dewi, Hani Puspita; Yasar, Watsiq (Proceeding International Conference on Religion, Science and Education, 2024)
The development of technology and the entry of the revolutionary era of society 5.0 is a challenge for social life. Current challenges need to be solved with technological innovation. in the current conditions, we need to provide knowledge related to skills in using technology both operating tools and developing devices. The impact of this era is the rapid development of technology in all sectors including the social work assistance process. This research leverages technological know-how in the development and application of more efficient and effective social work helping processes. The importance of preparing superior social workers in the digital era, it is necessary to integrate and develop technology in the social worker education process. Social workers must have good digital skills to face the current era. By using a literature study, this study aims to examine opportunities for social work interventions based on the demands of community needs 5.0. This study uses a qualitative approach by offering an overview of various social worker education reviews that are integrated with technological developments. The research method used is literature study by identifying various literatures. The selected literature is adapted to the topic of study, the code of ethics of social workers and knowledge of technology. Data analysis is sourced from relevant secondary data related to the development of digital technology and social worker education studies. This case study provides an overview for educators in social work education so they can play a bigger role in today’s technology-supported intervention development efforts. In addition, this study focuses on the development of social worker services in the technological era. In responding to the challenges of the current era, this study is relevant to be read by academics and social workers. The development of important technological engineering in the world of education and the development of social work interventions. In the education of social workers it is necessary to pay attention starting from the stages of engagement, assessment, planning, implementation of interventions, monitoring, evaluation and termination with the integration of today’s technology. This is done to make it more effective, initiative and professional in recommending service programs.